2015
DOI: 10.1186/s12989-016-0159-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulmonary exposure to gold core silver nanoparticles of different size and capping agents on cardiovascular injury

Abstract: BackgroundThe uses of engineered nanomaterials have expanded in biomedical technology and consumer manufacturing. Furthermore, pulmonary exposure to various engineered nanomaterials has, likewise, demonstrated the ability to exacerbate cardiac ischemia reperfusion (I/R) injury. However, the influence of particle size or capping agent remains unclear. In an effort to address these influences we explored response to 2 different size gold core nanosilver particles (AgNP) with two different capping agents at 2 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 68 publications
(81 reference statements)
0
22
0
Order By: Relevance
“…Our in vitro erythrocyte study is relevant to previous in vivo studies which demonstrated that exposure to AgNPs is associated with cardiovascular dysfunction in addition to cytotoxicity and oxidative stress [20,21]. We incubated the erythrocytes with vehicle or PVPor CT-AgNPs for 4 h; a time point similar to previous in vitro studies [18,31].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our in vitro erythrocyte study is relevant to previous in vivo studies which demonstrated that exposure to AgNPs is associated with cardiovascular dysfunction in addition to cytotoxicity and oxidative stress [20,21]. We incubated the erythrocytes with vehicle or PVPor CT-AgNPs for 4 h; a time point similar to previous in vitro studies [18,31].…”
Section: Discussionmentioning
confidence: 71%
“…In addition, coating has been reported to play an important role in NPs toxicity. In this context, in vivo studies have reported that polyvinylpyrrolidone (PVP) and citrate (CT) coated AgNPs induce tissue specific toxicity and aggravate cardiac ischemic reperfusion injury [20,21]. Moreover, a previous in vitro study has shown that PVPand CT-AgNPs induce toxicity in J774A.1 macrophage and HT29 epithelial cells [22].…”
Section: The In Vitro Effect Of Polyvinylpyrrolidone and Citrate Coatmentioning
confidence: 99%
“…These observations are congruent with previous experimental findings whereby exposure to PM alone induced minor or no observable changes in cardiac function. However, when PM exposure is paired to a secondary insult or stressor, PM is capable of exaggerating latent electrophysiological dysfunction (37) or worsening cardiac injury (25). Furthermore, it is possible that any changes associated with UFP induced modulation of ion channels leading to increased susceptibility to arrhythmogenesis would likely need greater than 24 hours to fully manifest (38).…”
Section: Discussionmentioning
confidence: 99%
“…Following the aspiration, the animal was returned to its cage and recovery was observed until normal grooming habits resumed. This form of oropharyngeal (OP) aspiration has been adopted by the members of the National Institute of Environmental Health Sciences Centers for Nanotechnology Health Implications Research (NCNHIR) and Nano GO consortiums in an efforts to minimize variability and is an accepted and previously published technique to achieve OP aspiration (2527). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation